Functions of Indirectness in American Idol Judges’ Comments - Malo, Raynesta Mikaela Indri (Journal of Language and Literature, 2016)
Indirectness is one of the most efficient ways to communicate each other. People use indirectness in communication for different purposes. The most discussed and discovered purpose across cultures is for politeness; people use language in indirect way to prevent hurting other’s feelings. In many cultures, indirectness is highly valued because saving face and harmony in social relationships are highly respected. This study is a descriptive study which is aimed at analyzing the functions or the purpose of using indirectness or indirect language in one of the rarely discussed realm of language use, a TV show, specifically, American Idol. The findings also reveal the strategiesused in order to perform the functions. The data is limited to the audition of American Idol season eight (8) which was held in 2009. There were 7 recordings for the 8 cities of audition. The totalnumber of data used in this study was 50 indirect comments. The result shows that there were 3 functions of the use of indirectness in the comments of the judges. The functions were (i) being ironic,(ii) being polite, and (iii) giving hints.Keywords: indirectness, politeness, judges’ comments